2022
DOI: 10.1039/d2nj01744j
|View full text |Cite
|
Sign up to set email alerts
|

In situ green synthesis of lysozyme/silver nanoparticles sol and their antimicrobial properties

Abstract: Silver nanoparticles (AgNPs) have been widely considered an ideal antimicrobial material due to their superior efficacy. However, it is prone to introduce toxic chemical reductants and stabilizers in the preparation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
1
5
1
Order By: Relevance
“…The protein and Ag + ions were mixed, they quickly combined, and specific amino acid residues in the protein reduced the captured silver ions under visible-light illumination to form metallic silver. Previous reports have shown that light accelerates electron loss, metal species reduction, and nanoparticle formation . This may be one of the reasons why xenon lamp irradiation promotes the formation of AgNPs, and its specific mechanism needs a further study.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The protein and Ag + ions were mixed, they quickly combined, and specific amino acid residues in the protein reduced the captured silver ions under visible-light illumination to form metallic silver. Previous reports have shown that light accelerates electron loss, metal species reduction, and nanoparticle formation . This may be one of the reasons why xenon lamp irradiation promotes the formation of AgNPs, and its specific mechanism needs a further study.…”
Section: Resultsmentioning
confidence: 96%
“…Previous reports have shown that light accelerates electron loss, metal species reduction, and nanoparticle formation. 24 This may be one of the reasons why xenon lamp irradiation promotes the formation of AgNPs, and its specific mechanism needs a further study.…”
Section: Mechanism Of the Synthesis Of Agnps Using Lyzmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriostatic nanomaterials are considered to be an effective option that can replace antibiotics in the treatment of bacterial infections. [4][5][6] In particular, nanocatalytic bacteriostatic materials have received widespread attention for the specific bactericidal properties due to the bacterial microenvironmental response properties. [7][8][9] In bacterial infection microenvironments (IME), transition metal nanomaterials with Fenton-like catalytic activity can convert endogenous H 2 O 2 into highly toxic reactive oxygen species (ROS) to destroy tumor cells or bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, AgNPs tend to agglomerate and tarnish in the colloidal phase, this trait may potentially compromise their stability and durability, which can in turn affect their sensing abilities. 17 To overcome these issues, different methods have been devised to stabilize AgNPs, including the deposition of the AgNPs on stable substrates like polymers, silica, or graphene oxide (GO). The objective of the current study was to entrap AgNPs onto GO sheets, as GO is known for its hydrophilicity, high surface area, mechanical strength, electrical conductivity, thermal stability, and chemical reactivity.…”
Section: Introductionmentioning
confidence: 99%